Wasu to Samaz: collective identity in Manyika nicknames - Pfukwa, Charles; Viriri, Advice (National University of Lesotho, 2016)
This paper explores linguistic innovation and onomastic aspects around the nicknames 'Samaz’ and ‘Wasu’. It goes on to examine place names like Samanyika and its derivatives in popular discourse. Nicknames are statements of identity and the identity can be collective or individual. Among these are issues of standardization, orality and phonological innovation of the nickname. Besides being derogatory and satirical, nicknames carry connotations and inherently own informal qualities of linguistic structure coupled with the phonetic sound. It is on the basis of a nickname that many positive and negative onomastic assumptions about the bearer can be inferred, as will be shown in the paper.